Drug Safety of Celecoxib - K. Hima Bindu; G. Venkat Rao (International Journal of Medical Research and Review, 2016)
Introduction: Non-steroidal anti-inflammatory drugs presently are the most widely used drugs in medicine and are the most frequent cause of adverse drug reactions, affecting multiple systems, mainly gastric, renal & cardiovascular, which is a major public health concern. Previous studies report, that selective COX-2 inhibitors are safer when compared to non-selective cyclooxygenase inhibitors. But, recent studies reveal, that the safety of these selective COX-2 inhibitors is not much better than that of conventional NSAIDs. In view of the wider usage of selective COX-2 inhibitor, celecoxib in day to day practice by many clinicians, the study has been taken up to report, whether selective COX-2 inhibitor celecoxib has got any advantages over conventional NSAIDs or not.Methodology: 15 patients were taken up for the study & all the patients were given celecoxib for 15 days. Both pre and post-treatment values of Hb%, blood urea, serum creatinine, serum bilirubin, bleeding time, clotting time, heart rate & blood pressure were recorded, tabulated & subjected to statistical analysis.Results: Selective COX-2 inhibitor, celecoxib has shown significant changes in bleeding time values & also good amount of gastric toxicity when assessed clinically. Hepatic, renal & other cardiovascular parameters were absolutely normal.Conclusion: In our short-term study, selective COX-2 inhibitor, celecoxib has shown good amount of gastric toxicity, showing no advantage over non-selective drugs. But, there is no hepatic, renal & cardiovascular toxicity.